COPING STRESS A WIFE WHO HAS A HUSBAND'S STROKE - Nasution, Mawaddah (Proceeding International Seminar of Islamic Studies, 2023)
Stroke is a type of disease that is very dangerous. A stroke is a medical condition that occurs when the blood supply to the brain is cut off or reduced. The cause of stroke can come from blood vessels or the rupture of blood vessels in the brain. This condition makes other people feel concerned about the sufferer. A husband is not the only one who suffers from this condition. A wife who is faced with this condition is expected to have great patience, provide sufficient attention to her husband, have the fortitude and ability to manage stress for the husband's continued recovery, and be able to share her attention with all family members. The purpose of this study is to examine the description of coping stress of a wife whose husband has had a stroke. The approach used is a descriptive-qualitative approach with data collection techniques such as observation, interviews, and documentation. The results obtained in this study showed that the wife used focused coping and religion to cope with stress problems in dealing with the condition of her husband, who had a stroke.